2014
DOI: 10.1063/1.4870472
|View full text |Cite
|
Sign up to set email alerts
|

Upconversion and pump saturation mechanisms in Er3+/Yb3+ co-doped Y2Ti2O7 nanocrystals

Abstract: Articles you may be interested inLuminescence thermometry below room temperature via up-conversion emission of Y2O3:Yb3+,Er3+ nanophosphors J.Intense green and red upconversion emission of Er3+,Yb3+ co-doped CaZrO3 obtained by a solution combustion reactionThe Er 3þ /Yb 3þ co-doped Y 2 Ti 2 O 7 nanocrystals were synthesized by the sol-gel method. X-ray diffraction, transmission electronic microscopy, and photoluminescence spectra were measured to verify the Y 2 Ti 2 O 7 nanocrystalline produced in the sample a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Hence, only the EBT process is inadequate to explain the results in our case. According to a recent study, the competition between UC and LD for the 4 I 13/2 manifold is very influential for the power-dependent luminescence. As the above four ET mechanisms are based on the UC as a depletion mechanism for the 4 I 13/2 manifold, it is reasonable to assume LD to be dominant depletion for the 4 I 13/2 manifold due to the low intrinsic phonon-energy matrix .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, only the EBT process is inadequate to explain the results in our case. According to a recent study, the competition between UC and LD for the 4 I 13/2 manifold is very influential for the power-dependent luminescence. As the above four ET mechanisms are based on the UC as a depletion mechanism for the 4 I 13/2 manifold, it is reasonable to assume LD to be dominant depletion for the 4 I 13/2 manifold due to the low intrinsic phonon-energy matrix .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Recently, it is found that the competition between UC and linear decay (LD) of the Er 3+ 4 I 13/2 manifold and 4 I 11/2 manifold is very important for determining the powerdependent relationship of corresponding emission manifolds. 37 A new UC mechanism with quantitative values for the rate constants involving Yb 3+ -to-Er 3+ ET UC out of the greenemitting manifolds was proposed to account for all the observed optical transitions, which provides a powerful tool for predicting the optical properties of the most widely studied UC phosphor and can also be applied in luminescent materials with the micro-and nanoscale. 38 While many Yb 3+ /Er 3+ codoped systems mainly focus on UC visible luminescence, there are only a few reports on their DS property, such as codoping effect on visible emission under 484 nm excitation, 24,33 DS visible emission in Yb 3+ /Er 3+ codoped systems under a variety of excitation scenarios, 39 and near-infrared (NIR) emission under 378 nm excitation 40 and so on.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Chen et al investigated the upconversion mechanism for two‐color emission in Er 3+ /Yb 3+ ‐doped ZrO 2 nanocrystals based on steady‐state rate equations and confirmed the efficient energy back‐transfer process 4 S 3/2 (Er 3+ ) + 2 F 7/2 (Yb 3+ ) → 4 I 13/2 (Er 3+ ) + 2 F 5/2 (Yb 3+ ) . Wang et al studied the energy‐transfer mechanism and established a theoretical model of Er 3+ /Yb 3+ codoped Y 2 Ti 2 O 7 based on the rate equations . A deeper understanding of the energy‐transfer mechanism is of great importance in optimal designs and practical applications of luminescent materials.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4 shows the pump power dependence of green and red UC emissions in 0.5% Tm 3+ and 1% Tm 3+ -groups with 0.5%, 5% and 20% Er 3+ doping under 980 nm excitation. According to the formula45: I uc  ∝  P n , where I uc is the output UC emission intensity, P is the infrared excitation power, n is the absorbed laser photon number when emitting an UC photon. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%